2022
DOI: 10.1002/ecs2.4008
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton functional composition determines limitation by nutrients and grazers across a lake productivity gradient

Abstract: Functional trade-offs among ecologically important traits govern the diversity of communities and changes in species composition along environmental gradients. A trade-off between predator defense and resource competitive ability has been invoked as a mechanism that may maintain diversity in lake phytoplankton. Trade-offs may promote diversity in communities where grazing-and resource-limited taxa coexist, which determines the extent to which communities are resource-or consumer-controlled. In addition, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Field observations (Cavender‐Bares et al, 2001; Li, 2002), experiments (Schulhof et al, 2019, 2022), and meta‐analyses (Marañón et al, 2012) have shown that the small‐celled algae tend to dominate phytoplankton communities in nutrient‐poor waters due to high nutrient uptake and use efficiency (Litchman et al, 2010). In contrast, aquatic systems generally display a shift toward the dominance of large‐celled algae in nutrient‐rich waters due to increased resistance to grazers (Litchman et al, 2010) as well as a competitive advantage under a high and fluctuating nutrient supply (Litchman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Field observations (Cavender‐Bares et al, 2001; Li, 2002), experiments (Schulhof et al, 2019, 2022), and meta‐analyses (Marañón et al, 2012) have shown that the small‐celled algae tend to dominate phytoplankton communities in nutrient‐poor waters due to high nutrient uptake and use efficiency (Litchman et al, 2010). In contrast, aquatic systems generally display a shift toward the dominance of large‐celled algae in nutrient‐rich waters due to increased resistance to grazers (Litchman et al, 2010) as well as a competitive advantage under a high and fluctuating nutrient supply (Litchman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Within a favorable water temperature range, rising water temperatures correspond to higher rates of phytoplankton growth (Baker and Geider, 2021). Changes in nutrient availability can significantly impact phytoplankton community structure, with growth rates being related to nutrient absorption rates under suitable water temperature and pH conditions (Schulhof et al, 2019;Villanova et al, 2021;Du et al, 2023). Hydrodynamic conditions also play a role in shaping phytoplankton community, as many phytoplankton are prone to thrive under stagnant water conditions (Li et al, 2013).…”
mentioning
confidence: 99%